A strategic approach to reducing mycoplasma testing costs - Gregoire, Zach (Kansas State University, 2018)
Mycoplasma; it is not a household name for many Americans or people around the world, but for those in the livestock industry, it has been a major concern. Mycoplasma, a member of the class Mollicutes, has had and continues to have a major impact on the cattle, swine and poultry industry, causing conditions such as arthritis, otitis media, reduced growth rate and reduced egg production (Journal of Veterinary Internal Medicine 2011) (Okwara 2016). This class of bacteria is unlike other classes, as defined by the lack of a cell wall, and is considered by many to be the smallest self-replicating prokaryote (Jack Maniloff 1992). Due to its small size, it can reside within cells and even pass through some of the currently used sterilizing filters in the biological/pharmaceutical industry today (Pall Corporation n.d.). This creates a risk for Mycoplasma contamination for those facilities/research centers that use materials of animal origin, as Mycoplasma organisms have historically been a common contaminate of cell lines and laboratory cultures, affecting roughly 15-35% of cell cultures (Cara N. Wilder 2015). An added concern is the difficulty in treatment of infected animals once an infection is established. The Mollicutes class has been considered innately resistant to the antibiotic penicillin and other cephalosporins due to the lack of the cell wall (Jack Maniloff 1992). Due to the clinical significance and risk factors surrounding the Mollicutes class, it is a current regulatory requirement to test materials of animal origin for the presence or absence of Mycoplasma. The specific criteria for the presence or absence of Mycoplasma test is dependent upon the country in which the product is intended to be sold. For the purposes of this study, the required method and products will be for those intended for sale domestically in the United States, or countries accepting US methodologies. To test a material or product for the presence or absence of Mycoplasma according to the current USDA code of federal regulations (CFR), the method is not a rapid procedure or a simple traditional broth inoculation. The domestic method is a minimum 24 day test that requires complex broth and agar media for Mycoplasma recovery. The complex media requirement is due to the fact that Mycoplasma organisms have stringent nutritional requirements due to their simplified cell structure/genome, which often require materials of animal origin, such as serums for lipid supply/metabolism (Jack Maniloff 1992). The 24 day Mycoplasma test requires an initial inoculation into the aforementioned broth and agar media and then 4 subsequent subcultures from the broth media onto the agar media at specified time intervals. All of the broth and agar media plates are incubated at specific atmospheric conditions and temperature for the duration of the test. The initial inoculation and subcultures are all examined by a trained Microbiologist at specific time intervals to search for evidence of viable Mycoplasma growth. The examination by a trained Microbiologist/technician is a vital step as Mycoplasmas do not produce turbidity in media, such as in traditional bacterial growth, nor are they visible by traditional light microscopy (Farzaneh 2011). If a Mycoplasma contamination is found, a biological/pharmaceutical company can pay huge sums of money to investigate the cause of the contamination, initiate corrective action, decontaminate the facility and destroy impacted batches. As evidenced by the above description, Mycoplasma testing places a large burden on a biological/pharmaceutical production facility or even research institutions. The complex media and labor cost for the 24 day test is extensive, which must be repeated for each batch of new material received or produced. The cost skyrockets if any contamination event occurs or even appears to occur, as investigation and decontamination add cost due to delay of release or possible destruction.
Keywords: Mycoplasma; Animal health; G CFR 113; Vaccine; Antibiotic